Improving the quality of processes by using knowledge continuity ensuring - Urbancová, Hana; Kříž, Josef (Univerzita Pardubice, 2012)
In the current knowledge economy the workers are the key competitive advantage and their knowledge is the most important asset in the various business processes. If people leave the organization they will take their knowledge with them and it can jeopardize the quality of the processes. This paper focuses on the topic of the ensuring the knowledge continuity as a tool for fluent improvement of processes in organizations. The processes and the areas were identified within the organization by means of induction. The processes are improved by using the knowledge continuity management. The benefits of the processes were measured by quantitative research, by using the questionnaire survey in organizations in the Czech Republic. One of the conclusions of the paper is that with correct knowledge continuity the quality of the processes in the organization can be increased together with the performance.
Keywords: knowledge; knowledge continuity; quality; process; benefits; quantitative survey